The determining factors of juvenile suicide - case of Kyrgyzstan: Factors Leading to Juvenile Suicidal Behavior - Bakiev, Erlan; Aliiaskarov, Bekchoro; Ismailov, Nurlan (Farabi Journal of Social Sciences, 2021)
In recent years, there is a rapid pace of growth in suicide and attempted suicide among youth in Kyrgyzstan, a small Central Asian country. The study aims to predict socio-economic, psychological, and other contextual determinants of suicide actions among youth based on a qualitative research through face-to-face interviewing. The research limits its scope with only the southern region of Kyrgyzstan, JalalAbad, where the suicide and attempt to suicide among youth in relation to general population was higher than other regions of the country. Nationwide research for the suicide among youth in Kyrgyzstan can be planned for future studies as a second phase of the project. Methods: For this research, parents, other close relatives, schoolteachers, neighbors and peers of victims are involved into a face-to-face interview. Additionally, the research also interviewed youth who chanced to survive after an attempt to suicide. Results: The results of the research indicate that many factors such as, social, economic and psychological that influence suicidal behavior among youth. Conclusion: However, the most influential were found to youth’s relationship with parents, teachers and peers; nonexistence of both parents (divorced, died) in the family, contagion, family income, psychological situations of youth and depression. Key words: Suicide, youth, parental affection, parental relationship, public policy, maltreatment, family income, peer relationship, teacher, and depression.